1989
DOI: 10.1111/j.1600-0765.1989.tb00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and crevicular fluid collagenase activity in the osseointegrated dental implant sulcus: A comparison of sites in edentulous and partially edentulous patients

Abstract: The soft tissues adjacent to osseointegrated dental implants (OII) were investigated using clinical, biochemical and microbiological methods. Tooth and implant crevices were compared in 15 partially edentulous patients, examining 28 peri-implant and 19 periodontal sites, and in 6 edentulous patients, examining 13 implant sites. Sites were classified by standard periodontal indices; the crevicular fluid flow determined; crevicular fluid was collected for collagenase assays; and the subgingival bacterial flora w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
199
5
13

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(233 citation statements)
references
References 45 publications
(10 reference statements)
13
199
5
13
Order By: Relevance
“…With this purpose, Gromatzky, Sendyk 15 (2002) established a modern protocol seeking to preserve osseointegration. The absence of relationship amongst the presence of pathogens, clinical signs of severe inflammation and history of periodontitis, observed in this research, contradicts reports of several authors 2,8,13,14,16,20,22,27 and the following considerations try to explain that discrepancy:…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…With this purpose, Gromatzky, Sendyk 15 (2002) established a modern protocol seeking to preserve osseointegration. The absence of relationship amongst the presence of pathogens, clinical signs of severe inflammation and history of periodontitis, observed in this research, contradicts reports of several authors 2,8,13,14,16,20,22,27 and the following considerations try to explain that discrepancy:…”
Section: Discussioncontrasting
confidence: 55%
“…PCR is also reproducible and relatively easy to execute as well as particularly valuable in the detection of non-cultivable organisms or those that are difficult to be distinguished in the cultivation 4,28 . The peri-implant sites of patients with periodontitis can present high concentrations of pathogens in the periodontal pockets 2,10,19,30 . Therefore, periodontal lesions considered irreversible can determine the indication of extraction of unhealthy teeth to avoid infection of future peri-implant sites 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However it has been noted that quality of tissue at the perimucosal region has little effect on the clinical indices. Lack of keratinized gingiva around implants did not result in higher gingival and bleeding indices or increased pocket depths (19). Parallel running supracrestal connective tissue fibres splice with circumferentially oriented fibres resulting in the formation of a mechanical cuff which provides an effective structural and functional seal.…”
Section: Epithelial Attachmentmentioning
confidence: 99%
“…Studies have shown similarities in the microflora from implant or tooth sites [12] [13] [14] [15]. High levels of periodontopathic bacteria including Porphyromonas gingivalis are said to be one of the major etiologic factors in human periodontitis [16] [17].…”
Section: Introductionmentioning
confidence: 99%